2004
DOI: 10.1099/vir.0.19623-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcription and promoter analysis of pif, an essential but low-expressed baculovirus gene

Abstract: The pif gene (per os infectivity factor) of Spodoptera littoralis nucleopolyhedrovirus (SpliNPV) encodes a structural protein essential for oral infection. This protein is expressed in very low quantities. In this study, transcription and promoter analysis of SpliNPV pif were carried out to understand more fully the regulation of pif gene expression. Transcription in the pif gene region was examined using RT-PCR, Northern blot, primer extension, ribonuclease protection and 39 RACE. The pif gene was encoded by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 54 publications
0
14
0
2
Order By: Relevance
“…We previously demonstrated that OBs produced by coinfecting insects with mixtures of complete (ϳ75%) and defective (ϳ25%) genotypes were ϳ2.5-fold more infectious than OBs comprising the complete genotype alone. The absence of PIF1 or PIF2 results in the complete loss of peroral infectivity in other NPVs (17,31,32,36,43). The lack of per os infectivity of both C and D genotypes was clearly due to the deletion of pif1 and pif2.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We previously demonstrated that OBs produced by coinfecting insects with mixtures of complete (ϳ75%) and defective (ϳ25%) genotypes were ϳ2.5-fold more infectious than OBs comprising the complete genotype alone. The absence of PIF1 or PIF2 results in the complete loss of peroral infectivity in other NPVs (17,31,32,36,43). The lack of per os infectivity of both C and D genotypes was clearly due to the deletion of pif1 and pif2.…”
Section: Discussionmentioning
confidence: 94%
“…The PIF proteins comprising PIF1, PIF2, and the recently identified PIF3 (Ac115) are found at low quantities in the envelopes of ODVs (1,9,17,25,31,43), together with an addition infection factor, P74 (10). This low level of expression is due to the weakness of its promoter, at least in the case of pif1 (17,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ORF5 and ORF2 are homologues of baculovirus ODV envelope protein-encoding gene odv-e56 (5) and of vp91, encoding a baculovirus protein of 91 kDa present in both the capsid and the envelope surrounding the capsid of ODVs (45). Baculovirus P74 and PIF-1 are present only in the ODV envelope (9,14,31). Even though PIF-2 and PIF- 3 have not yet been localized, it is conceivable that these functionally con- served proteins are also present in the ODV envelope.…”
Section: Resultsmentioning
confidence: 99%
“…Each gene in such cluster is transcribed from its respective promoter, resulting in a series of overlapping coterminal transcripts. In most cases, the overlapping transcripts generally share either a common 5Ј end (7,31) or a coterminal 3Ј end (1,12,13,21,27,28). Transcription of the distal upstream gene may interfere with the transcriptional initiation of the downstream gene via a regulatory mechanism called promoter occlusion (1,11,12,31).…”
Section: Discussionmentioning
confidence: 99%